Inter-Organisational Collaboration: A Qualitative Study of Collaboration Arrangements in the Public and Community Housing Sector in New Zealand - Mary Anne Teariki; Guy Penny; Philippa Howden-Chapman (Urban Science)
Complex problems are rarely solved on their own. One such problem facing Aotearoa New Zealand is the provision of affordable housing that enhances the wellbeing of tenants and local communities. Using qualitative methodology, this study examines the various ways in which public and community housing providers work together with external organisations to improve wellbeing. This research is the first of its kind in New Zealand to examine the different ways that housing providers collaborate with external organisations. It is also the first of its kind to explore the extent to which the Treaty of Waitangi (the founding document of New Zealand between Māori and the Crown) influences collaboration. To assist our understanding of collaboration typology, a focused literature review was undertaken, where a collaboration continuum was developed. The literature findings were utilised to strengthen our interrogation of the data by observing activities, rather than relying on commonly used terms. All housing providers were identified as investing heavily in collaboration. Those engaged in large complex projects exhibited higher levels of inter-organisational intensity. The Treaty of Waitangi was identified as influencing collaboration between housing providers and Māori, including non-Crown agencies. As the affordable housing sector undergoes changes, further research is recommended.